End-user Game Development Environments for Educators: Analyzing Platforms - Souza, Joana Gabriela Ribeiro De; Prates, Raquel Oliveira; Santos, Heloiza Aparecida (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
Games have been used for many years in educational contexts. They are called serious games. With the increasing presence of digital games in the everyday life of people and, therefore, of children and teenagers, educators sometimes adopt these games as part of their instructional activities. As educational games have a purpose beyond entertainment, educators sometimes want to use more than off-the-shelf games but also customize or create new games to suit their needs. However, developing games is a complex task involving aspects such as programming and game design. In this paper, we investigated what game-authoring tools aimed at educators for creating serious games offer to enable the creation and extension of educational games. We used the Semiotic Inspection Method to analyze two game authoring tools for educators - Rufus and <u-Adventure>. We contrasted our results with a study focusing on general-purpose game authoring tools and identified specific constructs and strategies to support end-users that the platforms we analyzed adopted for the educational context, in addition to those identified in general-purpose tools.